Flood hazard mapping using fractal dimension of drainage network in Hamadan City, Iran. Issue 4 (December 2017) - Malekinezhad, Hossein; Talebi, Ali; Ilderomi, Ali Reza; Hosseini, Seyed Zeynalabedin; Sepehri, Mehdi
Abstract : Recently a large number of cities in the province of Hamadan in Iran have been affected by several storm-flood events, causing hundreds of people to be evacuated from their homes. One of the reasons that has markedly increased the flood hazard magnitude in the city of Hamadan relates to the suburban basins in the upper areas of the study area. In relation to the flood hazard and the significance of the suburban basins, the correlation between the geomorphological characteristics of the river system and the probability of flooding was primarily investigated. In order to assess the geomorphological characteristics of the river system and evaluate their relationship with flooding for five suburban basins, and in order to measure the accuracy of the fractal dimension in determining flood hazard and the significance of the characteristics, the Soil Conservation Service (SCS) method was also employed. The comparative results of the two employed methods demonstrated nearly the same outcome. Using the fractal dimension, suburban basins 2 and 3 showed the maximum and minimum fractal dimensions, respectively. In the SCS method, these two suburban basins exhibited, respectively, the maximum and minimum flood hazard values. In addition, suburban basins 4 and 5 revealed virtually the same fractal dimension.